Influence of Light-Curing Time and Increment Thickness on the Properties of Bulk Fill Composite Resins With Distinct Application Systems - Carlos Rocha Gomes Torres; Taiana Paola Prado; Daniele Mara da Silva Ávila; Cesar Rogério Pucci; Alessandra Bühler Borges (International Journal of Dentistry)
The objective of this study was to evaluate the influence of light-curing time and increment thickness on the microhardness and degree of conversion (DC) of bulk fill composite resins with different application systems. Translucency parameter (TP) was also measured. Specimens of resin composites were prepared in a circular matrix using a single increment with different thicknesses (2, 4, and 6 mm) and light-cured with distinct times (10, 20, and 40 s). The materials tested (n = 5 pergroup) were Filtek One (FO) bulk fill, Tetric N-Ceram (TC) bulk fill, SonicFill 3 (SF), VisCalor (VC) bulk. After 24 h, Knoop microhardness (KN) was measured, and the bottom/top ratio (B/Tratio) was calculated. The DC was measured using Fourier transformed infrared (FTIR) spectroscopy. The TP was assessed in additional specimens with 1 mm thick (n = 5). The data were statistically analyzed with analysis of variance (ANOVA) and Tukey’s tests (5%). Significant differences were observed for all factors, for both B/Tratio and DC (p <0.05). The higher increment thickness and the lower curing times resulted in lower B/Tratio and DC means. The VC and TC resins exhibited the overall higher B/Tratio, and the highest TP. SF presented the lowest values of B/Tratio and DC, with compromised polymerization at 6 mm depth. TP (means ± SD) were FO (12.85 ± 1.0)1, SF (15.62 ± 0.73)2, TC (20.32 ± 0.49)3, and VC (20.53 ± 0.73)3. We concluded that the greater the thickness of the increment, the lower the DC. Higher light curing times resulted on increased DC of the tested composites. The higher translucent materials VC and TC showed the greater B/Tratio; and FO resin exhibited the higher DC values.